Testing and modelling of masonry creep and damage in uniaxial compression - Pina-Henriques, J. (2003)
The problems related to the analysis of ancient constructions are gigantic due to the difficulties in characterizing the geometry, the materials, the sequence of construction, the existing damage and the building processes.A difficult aspect in the repair and strengthening of existing structures is the long term loading of masonry in compression. Safety assessment has been greatly influenced by the collapse of monumental buildings in the last decade, where creep behaviour and creep-fatigue interaction proved to be of relevance for massive masonry walls. Experimental tests on masonry creep have been recently carried out, together with numerical implementations. Both testing and numerical modelling of multi-leaf masonry walls need still more research.Experimental testing on the creep of regular ancient masonry together with numerical modelling is currently under investigation and is briefly addressed in the paper. In addition, a discussion of the load transfer between masonry components is given. This represents a contribution for understanding creep behaviour and load transfer mechanisms in multi-leaf walls.